TRANSFORMASI DIGITAL DALAM APLIKASI SERANG BAHAGIA: UPAYA PENINGKATAN PELAYANAN PUBLIK DI UPT DUKCAPIL KECAMATAN KRAGILAN KABUPATEN SERANG - Mardiana, Rani; Bangsawan, Try Adhi; Amilia, Rizki (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to analyze the implementation of digital transformation through the Serang Bahagia Application as a public service innovation at the Population and Civil Registration Technical Implementation Unit (UPT Dukcapil) in Kragilan District, Serang Regency. The background of this study is based on the community's need for fast, efficient, and transparent public services in the digital era. The research method uses a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The research analysis refers to Indrajit's (2006) theory, which emphasizes three indicators of successful digitization, namely support, capacity, and value.The results of the study show that the Serang Bahagia application has provided easy access to population services, increased the efficiency of administrative processes, and strengthened the transparency of public services. However, challenges are still encountered in the form of limited digital literacy among the elderly, uneven network infrastructure in remote areas, and a lack of intensive socialization. Nevertheless, the use of this application has had a positive impact on improving the quality of public services in Kragilan District. This study confirms that the digitization of public services through the Serang Bahagia application has great potential to improve service quality, but it needs to be optimized through improving human resource competencies, strengthening digital infrastructure, and broader socialization.